Small Firm Survival and Innovation: An Evolutionary Approach. (May 2013) - Dobson, Stephen; Breslin, Dermot; Suckley, Louise; Barton, Rachel; Rodriguez, Liliana
This paper explores 'evolution' as a means of complementing our understanding and interpretation of creative innovation networks in small firms. The abstracted evolutionary mechanisms of variation, selection and retention (VSR) are employed to add a more dynamic interpretative framework to the reading of social networks and group structures. The paper thus presents a lens through which to appreciate creativity as an evolving and shared process. The principal aim of this research is to illustrate otherwise tacit informal relations within a small business through the application of a qualitative approach to social network analysis (SNA) and, in doing so, to present intra-firm relations as central to creativity and innovation – particularly as the organizational structure moves beyond the dominance of the founding entrepreneur.